Sexual dimorphism in the size and shape of the raptorial pedipalps of Giant Whip Spiders (Arachnida: Amblypygi) - McLean, C.J.; Garwood, R.J.; Brassey, C.A. (Journal of zoology (1987), 2020)
Sexual dimorphism in the form of elaborate crests, horns and swellings can be a clear indicator of the differing evolutionary pressures to which males and females are subject. However, dimorphism can also be expressed in more subtle shape differences not outwardly obvious to the observer. Whip spiders (Amblypygi) possess a unique pair of spined pedipalps hypothesized to primarily function in prey capture, but also serving multiple other functions. Little is known regarding the intraspecific shape variation of these limbs and its potential causes. Because a role during courtship and male contest has also been hypothesized, sexual selection may contribute to shape differences. As such, we hypothesize that sexual dimorphism will be present in the size and shape of amblypygid pedipalps, with male contest selecting for longer and thicker pedipalps, and larger spines in males. This study aims to test this hypothesis, by quantifying the contribution of ontogeny and sexual dimorphism to shape within the raptorial pedipalps of Damon variegatus. Discriminant function analysis using GMM landmark data reveals statistically significant sexual shape dimorphism in both the tibia and femur of the pedipalp. Contrary to our hypothesis, males display a more gracile pedipalp morphology with reduced spination. Sex differences in the allometric slope and overall size were also found in a number of linear appendicular metrics using Type‐II regression. Males have statistically longer pedipalp tibiae, whip femora, and leg two femora. We propose that males have evolved a longer pedipalps in the context of display contest rather than physical aggression. The elongation of structures used in display‐based contest and courtship found herein further emphasizes the contribution of visual cues to the evolution of morphology more broadly. Our study uses geometric morphometrics to quantify sexual size and shape differences in the raptorial pedipalps of whip spiders for the first time. We determine that male Damon variegatus display a more gracile pediplap morphology, with a thinner central shaft and smaller spines. We hypothesize that the male pedipalp morphology is not primarily optimised for prey capture, but instead aids in display based contest.